Efficacy and Safety of Vernakalant for Cardioversion of Recent-onset Atrial Fibrillation in the Asia–Pacific Region: A Phase 3 Randomized Controlled Trial. Issue 2 (February 2017) - Beatch, Gregory N.; Bhirangi, Kiran; Juul-Moller, Steen; Rustige, Jörg
Abstract : Abstract: Atrial fibrillation (AF) is a common clinically significant cardiac arrhythmia. This phase 3 randomized, double-blind, placebo-controlled trial assessed the efficacy and safety of vernakalant hydrochloride for the pharmacological conversion of AF to sinus rhythm in patients with recent-onset (>3 hours to ⩽7 days) symptomatic AF from the Asia–Pacific region. Patients received an infusion of vernakalant (3 mg/kg) or placebo for 10 minutes. If AF had not been terminated 15 minutes later, a second infusion of vernakalant (2 mg/kg) or placebo for 15 minutes was administered. The primary efficacy end point was conversion of AF to sinus rhythm for >1 minute within 90 minutes. The study was terminated early for administrative reasons; 123 patients from Korea, Taiwan, and India were randomized to receive vernakalant (n = 55) or placebo (n = 56). A greater proportion of patients who received vernakalant (52.7%) than placebo (12.5%) met the primary end point ( P < 0.001), and cardioversion was faster in the vernakalant group than in the placebo group ( P < 0.001). Vernakalant was generally well tolerated; the incidence of treatment-emergent adverse events was similar between the groups. We conclude that vernakalant is efficacious in the rapid cardioversion of recent-onset AF in patients from the Asia–Pacific region.